CVD-Diamond Coating as Wear Protection for Standard Heat-Treatable Steel - Kellermann, Karsten; Fandrey, Jan; Rosiwal, Stefan; Singer, Robert (International Symposium on Friction, Wear and Wear Protection 2008, 2011)
Keywords: CVD-diamond coating; Standard heat-treatable steel; Wear protection

Influence of surface roughness on the tribological properties of HF-CVD diamond coated heat-treatable steel - Kellermann, Karsten; Erhardt, S.; Fandrey, Jan; Rosiwal, Stefan; Singer, Robert (Wear, 2010)
Standard heat-treatable C35 (1 0501) steel specimens were pre-coated with diffusion chromium carbide interlayer and in second step a crystalline diamond film was applied by Hot-Filament Chemical Vapour Deposition This study investigates the tribological properties of specimens that were treated mechanically in a different way before the coating in order to achieve a different roughness The tests were performed in a water lubricated ring-on-disc configuration while the coefficient of friction was measured Wear analysis was done by light microscope The wear development was obtained by several stops during testing The friction and wear developments are compared and discussed for different surface roughness Pre-treatment of the steel surface has a great influence on the tribological properties of the CVD diamond coating especially the evenness of the surface determines the real contact area and therefore the wear behavior (C) 2010 Elsevier B V All rights reserved
Keywords: HF CVD diamond; Steel; Surface roughness; Wear; Evenness

In-situ tensile testing of crystalline diamond coatings using Raman spectroscopy - Ahmed, Furqan; Durst, Karsten; Rosiwal, Stefan; Fandrey, Jan; Schaufler, Jens; Göken, Mathias (Surface & Coatings Technology, 2009)
In the present work, the fracture behaviour of crystalline diamond thin films on titanium substrate has been studied under uniaxial in-situ tensile loading in Micro-Raman spectroscopy. Thin crystalline diamond films were deposited onto thin titanium foils using a hot filament chemical vapour deposition technique. The in-situ investigations in Raman spectroscope indicated that the internal stresses, which were compressive at the beginning, can be reduced by the application of tensile load. At higher strain values, when internal stresses were of tensile nature, cracks were formed in the coating with reduced crack spacing at higher strains and also the tensile stress stayed constant during cracking. Cross-section analyses, across tensile cracks, with a focused ion beam microscopy showed that the crack starts from the surface of the coating, then propagates into the interlayer, stops at the surface of the metallic substrate and opens up on further straining without delamination. This cracking behaviour indicates a good adhesion of the coating to the substrat